Kinetics of chemical processes - Boudart, Michel (Butterworth-Heinemann series in chemical engineering., 1991)
Kinetics of Chemical Processes details the concepts associated with the kinetic study of the chemical processes. The book is comprised of 10 chapters that present information relevant to applied research.